PENGARUH NILAI, KUALITAS PELAYANAN, PENGALAMAN PELANGGAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN - Timotius Hendra (Jurnal Bisnis dan Manajemen, 2017)
The research aims examine  and analyze the effect of perceived value, service quality, customer experience  on customer satisfaction and customer loyalty, the research also examine and analyze effect of perceived value, service quality, customer experience on customer loyalty by mediate of customer satisfaction. This type of research is explanatory research while collecting primary data through distribution of questionnaires to customer in Giant Supermarket Sawojajar Malang as many as 120 customers. Sampling technique used is purposive sampling. In this case, the independent variable are perceived value, service quality, customer experience, as well as intervening variable is customer satisfaction. while dependent variable is customer loyalty. The data has been collected then analysed by using analysis of PLS (Partial Least Square). The result obtained are perceived value has effect on customer satisfaction, service quality has effect on customer satisfaction, customer experience has effect on customer satisfaction, customer satisfaction has effect on customer satisfaction, perceived value has effect on customer loyalty, service quality has effect on customer loyalty, customer experience has effect on customer loyalty, perceived value has effect on customer loyalty by mediate of customer satisfaction, service quality has effect on customer loyalty by mediate of customer satisfaction, customer experience has no effect on customer loyalty by mediate of customer satisfaction DOI : https://doi.org/10.26905/jbm.v4i2.1694